2018
DOI: 10.4049/jimmunol.1700156
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Low-Affinity TCRs Support Regulatory T Cell Function in Autoimmunity

Abstract: Regulatory T cells (Tregs) use a distinct TCR repertoire and are more self-reactive compared with conventional T cells. However, the extent to which TCR affinity regulates the function of self-reactive Tregs is largely unknown. In this study, we used a two-TCR model to assess the role of TCR affinity in Treg function during autoimmunity. We observed that high- and low-affinity Tregs were recruited to the pancreas and contributed to protection from autoimmune diabetes. Interestingly, high-affinity cells prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Apparently Tregs with low-affinity TCR are more likely to use non-TCR-dependent suppressive mechanisms in the absence of strong TCR signaling in response to humoral inflammatory factors, while high-affinity Tregs preferentially upregulate TCR-dependent regulatory molecules, such as CTLA-4, TIGIT, and IL-10. Nevertheless, both types of cells have suppressive potential and support autotolerance and immune equilibrium (31,57,58).…”
Section: Treg Heterogeneitymentioning
confidence: 99%
“…Apparently Tregs with low-affinity TCR are more likely to use non-TCR-dependent suppressive mechanisms in the absence of strong TCR signaling in response to humoral inflammatory factors, while high-affinity Tregs preferentially upregulate TCR-dependent regulatory molecules, such as CTLA-4, TIGIT, and IL-10. Nevertheless, both types of cells have suppressive potential and support autotolerance and immune equilibrium (31,57,58).…”
Section: Treg Heterogeneitymentioning
confidence: 99%
“…Such an assumption is further supported by a study using a NOD‐based model of autoimmune diabetes. This study demonstrated that T reg populations with a low‐affinity TCR for their cognate antigen preferentially expressed Amphiregulin, preferentially localized to the site of inflammation and functioned there in an antigen‐independent way . Thus, taken together, the combined expression of T1/ST2 and EGFR may enable tissue‐resident T reg populations to function in a MHC‐II‐independent way.…”
Section: The Function Of Regulatory T‐cell‐derived Amphiregulinmentioning
confidence: 82%
“…This study demonstrated that T reg populations with a low-affinity TCR for their cognate antigen preferentially expressed Amphiregulin, preferentially localized to the site of inflammation and functioned there in an antigen-independent way. 57 Thus, taken together, the combined expression of T1/ST2 and EGFR may enable tissue-resident T reg populations to function in a MHC-II-independent way. In Th2 cells, the induced expression of Amphiregulin, in an autocrine way, enabled the formation of such hetero-complexes between EGFR and T1/ST2, and only upon expression of Amphiregulin could activated Th2 cells function in a MHC-II-independent way.…”
Section: The Function Of Regulatory T-cell-derived Amphiregulinmentioning
confidence: 99%
“…A further layer of variables, not addressed in this analysis, lies in the fact that multiple different clones of T cells may have TCR that bind the same TCEM peptide motif but with different affinities, and hence different dwell times, and that may trigger different cytokine outcomes ( 106 ). Higher binding affinity, consistent with higher suppressive indices, is reportedly more prone to generate IL-10 upregulation ( 106 , 107 ). Binding based on less than five amino acid residues, or so-called “near neighbor” binding, further expands the possibilities for lesser binding affinities ( 108 ).…”
Section: Discussionmentioning
confidence: 99%